ANALISIS HUBUNGAN BIG FIVE PERSONALITY DAN KOMITMEN ORGANISASI SERTA PENGARUHNYA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Studi Pada Karyawan Dinas Kesehatan Kota Salatiga) - Maghfironsyah, Fadhil Alinurda; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2019)
The population used in this study are all employees who work in Salatiga Health Office that have worked for at least 2 years. The number of samples used in this study were 185 respondents. The method of data collection is done through a questionnaire. This study uses Structural Equation Modeling (SEM) analysis techniques using AMOS 20 analysis tools. The results showed that there was a significant and positive relationship between big five personality towards organizational commitment and there were significant and positive influences big five personality towards organization citizenship behavior and organizational commitment to organization citizenship behavior to employees at the Salatiga Health Office.